A Review on Risk Factors,Staging and Survival Rates of Endometrial Cancer in Both Black and White Women in Infertility Patients in USA (World Journal of Current Medical and Pharmaceutical Research, 2020)
This article is focused mainly on risk factors,staging and survival rates of endometrial cancer in infertility patients in both black and white women in United States, These risk factors split in to two groups  such as exogenous& endogenous. Exogenous mainly (fertility treatment clomiphene, tamoxifen, human chorionic gonadotropins,human menopausal Gonadotropins& Birth control pills, intra uterine devices) These factors which increases the concentrations of unopposed estrogen for a short periods of time but  successful leads to fertility, long-term leads to endometrial cancer, and endogenous risk factors includes mainly (Poly cystic ovary syndrome, Obesity,Diabetes, and Hypertension) these risk factors in infertility women may lead to increased unopposed estrogen in the body may leads  to development of endometrial cancer over a period of time. It is the commonest reproductive cancer. Our objective was toassess association between exogenous and endogenous risk factors, in infertility patients staging and survival rates in infertility patients which leads to an endometrial cancer .It is estimated that by 2030, endo metrialcancer will become the 6th most common cancer overall, and the 3rd most common among women. In addition, five year survival after an EC diagnosis is lower for black women when compared to white women at every stage of diagnosis. “Early detection leads to early prevention”.